Pharmacist and physician insight of vancomycin therapeutic drug-monitoring changes. Issue 1 (16th September 2022) - Gregory, Eric R.; Stun, Lucy; Mason, Matt J.; Wilson, Nicole M.; Hammoud, Kassem A.
Abstract: The updated vancomycin guideline for treatment of serious methicillin-resistant Staphylococcus aureus infections prompted institutions to convert from trough to area-under-the-curve monitoring. The physician perception of the transition, coupled with that of pharmacists, was measured by pre- and postimplementation surveys. Both groups believed safety would be increased without efficacy changes.